Transmission shaft and bearing device using the same
The transmission shaft with a diffusion layer and iron tetraoxide coating addresses the limitations of existing methods by enhancing surface damage resistance and fatigue strength, while simplifying the manufacturing process, thereby extending the lifespan of transmission shafts and bearing devices.
Patent Information
- Application Number
- JP2021133926
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-08-19
AI Technical Summary
Existing methods for extending the life of bearings in foreign matter environments or under lean lubrication, such as carbonitriding treatment and shot peening, are either insufficient in achieving a long lifespan or complicate the manufacturing process due to the need for individual product processing.
A transmission shaft with a raceway surface for needle rollers, made from chromium steel or similar, featuring a diffusion layer with iron carbides, nitrides, and carbonitrides, and an iron tetraoxide coating. This configuration enhances surface damage resistance and fatigue strength while simplifying the manufacturing process.
The proposed solution extends the lifespan of transmission shafts and bearing devices by improving surface damage resistance and fatigue strength, while also simplifying the manufacturing process, thus achieving a balance between performance and production efficiency.
Smart Images

Figure 0007657119000005 
Figure 0007657119000006 
Figure 0007657119000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a transmission shaft and a bearing device using the same. [Background technology]
[0002] In a speed changer such as a transmission, a bearing assembly is used that is a set of a shaft whose outer diameter portion serves as a raceway surface and a needle roller bearing with a cage that is placed on the outer circumference of the shaft. This bearing assembly is used in an environment where there is high temperature and a lot of foreign matter such as wear powder. For this reason, this bearing assembly requires parts that are resistant to surface damage caused by foreign matter or poor lubrication. In particular, the shaft is a fixed part, so it has a structure in which the same points are always damaged, and it is likely to be the weakest point.
[0003] A commonly known method for extending the life of bearings in foreign-contamination environments or with low lubrication is to subject steel components to heat treatment (carbonitriding) in a carbonitriding atmosphere containing ammonia (NH3) to increase the amount of retained austenite and the concentrations of carbon and nitrogen on the surface.
[0004] In addition, a technique for forming recesses in a shaft or roller by shot peening and coating the recesses with a solid lubricant to reduce the coefficient of friction is disclosed, for example, in JP 2006-161887 A (Patent Document 1). Similarly, a technique for forming a hardened layer (Hv850 or more and Hv10000 or less) on the surface by shot peening and providing a large compressive residual stress (absolute value 600 MPa or more and 1700 MPa or less) to strengthen the surface is disclosed, for example, in JP 2017-106534 A (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-161887 A [Patent Document 2] JP 2017-106534 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, a sufficient life cannot be obtained by general carbonitriding alone. Furthermore, the life extension method involving shot peening as in Patent Documents 1 and 2 requires individual treatment for each product, which complicates the manufacturing process.
[0007] The present invention has been made to solve the above-mentioned problems, and its object is to provide a transmission shaft that can be manufactured using a simple process to achieve a long service life, and a bearing device using the same. [Means for solving the problem]
[0008] The transmission shaft of the present invention is used in a transmission and has a raceway surface on which needle rollers roll, and includes a base material and a black oxide coating. The base material is made of any one of chromium steel, chromium molybdenum steel, and nickel chromium molybdenum steel, and has a diffusion layer on its surface that contains crystal grains of at least one of iron carbide, iron nitride, and iron carbonitride. The black oxide coating is formed on the surface of the base material and is disposed on at least the raceway surface.
[0009] In the present invention, the transmission may be either a speed reducer or a speed increaser.
[0010] In the above-mentioned transmission shaft, the thickness of the black oxide film is 1 μm or more and 2 μm or less.
[0011] In the above-mentioned transmission shaft, the base material is made of chrome-molybdenum steel.
[0012] In the above-mentioned transmission shaft, the average grain size of the prior austenite crystal grains on the surface of the base material is 8 μm or less.
[0013] In the above transmission shaft, the area ratio of the compound grains including at least one crystal grain in the diffusion layer is 3% or more, and the average grain size of the compound grains is 0.3 μm or less.
[0014] In the above-mentioned transmission shaft, the diffusion layer includes a plurality of martensite blocks.
[0015] In the above-mentioned transmission shaft, the maximum grain size of the martensite blocks is 3.8 μm or less.
[0016] A bearing device of the present invention includes the above-mentioned transmission shaft and a plurality of needle rollers that roll on the raceway surface of the transmission shaft.
[0017] The method for manufacturing a transmission shaft of the present invention is a method for manufacturing a transmission shaft used in a transmission and having a raceway surface on which needle rollers roll, and includes the following steps.
[0018] A steel material made of any one of chromium steel, chromium-molybdenum steel, and nickel-chromium-molybdenum steel is prepared. The steel material is carbonitrided. A black oxide film is formed on the surface of the carbonitrided steel material.
[0019] In the above-mentioned method for manufacturing a transmission shaft, the steel material is made of chromium molybdenum steel. The step of carbonitriding the steel material includes a step of heating the steel material to 930°C or more and 940°C or less in a carbonitriding atmosphere containing ammonia. The carbonitrided steel material is heated to a primary quenching temperature of more than 850°C and less than 930°C, and then cooled to a temperature equal to or less than the Ms point, thereby performing primary quenching. The steel material which has been primarily quenched is heated to a secondary quenching temperature of more than the A1 point and less than 850°C, and then cooled to a temperature equal to or less than the Ms point, thereby performing secondary quenching. Effect of the Invention
[0020] According to the present invention, it is possible to realize a transmission shaft that can be manufactured through a simple process and has a long service life, and a bearing device using the same. [Brief description of the drawings]
[0021] [Figure 1] 2 is a partially cutaway perspective view showing a planetary gear and its support structure in a planetary transmission with the planetary gear cut away. FIG. [Diagram 2] FIG. 2 is a cross-sectional view of the planetary gear and its support structure shown in FIG. [Diagram 3] 3 is an enlarged cross-sectional view showing the configuration of a transmission shaft in a region R in FIG. 2. [Figure 4] FIG. 4 is a flow diagram showing a method for manufacturing a transmission shaft according to one embodiment. [Diagram 5] FIG. 5 is a flow chart showing a detailed breakdown of the carbonitriding heat treatment steps in FIG. 4. [Figure 6] 5 is a graph showing a heat pattern in a method for manufacturing a transmission shaft according to one embodiment. [Figure 7] 4A is a diagram showing the driving force of a needle roller and the load distribution acting on the raceway surface when the raceway surface is straight (A) and when there is deflection on the raceway surface (B). FIG. [Figure 8] 1 is a graph showing the results of measuring the carbon concentration and nitrogen concentration of Sample 1 by EPMA. [Figure 9] 1 is a graph showing the results of measuring the carbon concentration and nitrogen concentration of Sample 2 by EPMA. [Figure 10] 1 is an electron microscope image of the vicinity of the surface of sample 1. [Figure 11] 1 is an electron microscope image of the vicinity of the surface of sample 2. [Figure 12] 1 is an optical microscope image of the vicinity of the surface of sample 1. [Figure 13] 1 is an optical microscope image of the vicinity of the surface of sample 2. [Figure 14] 1 is a graph showing the average grain sizes of martensite blocks belonging to the third and fifth groups in the vicinity of the surface of Sample 1 and Sample 2. [Figure 15] 1 is a graph showing the average aspect ratios of martensite blocks belonging to groups 3 and 5 in the vicinity of the surfaces of samples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the following drawings, the same or corresponding parts are designated by the same reference characters, and overlapping descriptions will not be repeated.
[0023] <Planetary gears in planetary transmissions and their support structure> First, a planetary gear and a support structure thereof in a planetary transmission according to one embodiment will be described with reference to Figs.
[0024] Fig. 1 is a partially cutaway perspective view of a planetary gear and its support structure in a planetary transmission, with the planetary gear cut away, Fig. 2 is a cross-sectional view of the planetary gear and its support structure shown in Fig. 1.
[0025] A planetary transmission has a planetary gear set. The planetary gear set has three gear systems: a sun gear, planetary gears, and an internal gear. In a planetary gear set, the required speed change is performed by fixing or releasing one of the gears in the other two systems in response to the input to the gear in one system.
[0026] As shown in FIG. 1, the planetary gear 4 has a plurality of teeth 4a on its outer periphery. The teeth 4a of the planetary gear 4 mesh with teeth provided on the outer periphery of a sun gear (not shown). As a result, the planetary gear 4 rotates on the outer periphery of the sun gear. The teeth 4a of the planetary gear 4 also mesh with teeth provided on the inner periphery of an internal gear (not shown). As a result, the planetary gear 4 rotates on the inner periphery of the internal gear. In this way, the planetary gear 4 revolves around the axis of the sun gear between the sun gear and the internal gear.
[0027] The planetary transmission has a rolling bearing device 10 that rotatably supports a planetary gear 4. The rolling bearing device 10 has a transmission shaft 1, a plurality of needle rollers 2, and a cage 3. The rolling bearing device 10 may also include the planetary gear 4.
[0028] A through hole is provided in the center of the planetary gear 4. A wall surface 4b defining the through hole constitutes the inner peripheral surface of the planetary gear 4. The transmission shaft 1 is inserted into the through hole of the planetary gear 4. As a result, the planetary gear 4 surrounds the outer periphery of the transmission shaft 1. The transmission shaft 1 has, for example, a cylindrical shape. The transmission shaft 1 has an oil passage 1a therein. The transmission shaft 1 corresponds to the inner member of the rolling bearing device 10, and the planetary gear 4 corresponds to the outer member of the rolling bearing device 10. A needle roller bearing with a cage is arranged between the outer peripheral surface (raceway surface 1b) of the transmission shaft 1 and the inner peripheral surface (raceway surface 4b) of the planetary gear 4.
[0029] The needle roller bearing with cage has a plurality of needle rollers 2 and a cage 3. The cage 3 has an annular shape and surrounds the outer circumferential surface of the transmission shaft 1. The cage 3 has a plurality of pockets 3a. The multiple pockets 3a are arranged at approximately equal intervals along the circumferential direction. A needle roller 2 is held in each of the multiple pockets 3a so that it can roll freely.
[0030] 2, each of the multiple needle rollers 2 is arranged to roll on its outer peripheral surface which forms the raceway surface 1b of the transmission shaft 1 and its inner peripheral surface which forms the raceway surface 4b of the planetary gear 4. The planetary gear 4 is supported rotatably on the transmission shaft 1 by a needle roller bearing with a cage.
[0031] Although a gear type transmission has been described as an application example of the transmission shaft, the present invention can also be applied to belt type, toroidal type, hydraulic type, and other transmissions.
[0032] <Configuration of transmission shaft 1> Next, the configuration of the transmission shaft 1 will be described with reference to FIG.
[0033] Fig. 3 is an enlarged cross-sectional view showing the configuration of the transmission shaft in region R in Fig. 2. As shown in Fig. 3, the transmission shaft 1 has a base material 11 and a black oxide coating 12. The base material 11 is made of, for example, a steel material containing chromium. The base material 11 is made of, for example, any one of chromium steel, chromium molybdenum steel, and nickel chromium molybdenum steel. The chromium steel, chromium molybdenum steel, and nickel chromium molybdenum steel mentioned above are steels belonging to the SCr steel type, SCM steel type, and SNCM steel type, respectively, defined in the JIS (Japanese Industrial Standards) standard (JIS G 4053:2016).
[0034] The base material 11 has been subjected to carbonitriding heat treatment. Therefore, the base material 11 has a diffusion layer DR on its surface (outer circumferential surface). The diffusion layer DR is a portion in which the concentrations of nitrogen and carbon are higher than the concentrations of nitrogen and carbon in the steel material (inner IP than the diffusion layer DR) constituting the transmission shaft 1. The depth D of the diffusion layer DR is, for example, 0.6 mm or more and 1.5 mm or less.
[0035] The diffusion layer DR has a plurality of compound grains. The compound grains are at least one crystal grain of iron (Fe) carbide, iron nitride, and iron carbonitride. More specifically, the compound grains are crystal grains of a compound in which a part of the iron site of cementite (Fe3C) is replaced by chromium and a part of the carbon (C) site is replaced by nitrogen (N) (i.e., a compound represented by (Fe,Cr)3(C,N)).
[0036] The black iron tetroxide film 12 is disposed in contact with the surface of the base material 11. The black iron tetroxide film 12 is made of black iron tetroxide (Fe3O4) and is known as black rust, which is a passive oxide film. The surface of the black iron tetroxide film 12 is porous. The thickness of the black iron tetroxide film 12 is 1 μm or more and 2 μm or less. The black iron tetroxide film 12 is disposed on at least the raceway surface 1b of the transmission shaft 1. The black iron tetroxide film 12 may be disposed so as to cover the entire surface of the base material 11.
[0037] The black oxide film 12 is formed on the surface of the base material 11 by a chemical conversion treatment called black dye treatment, for example. The black dye treatment in this embodiment involves immersing the base material 11 in a strong alkaline aqueous solution containing sodium hydroxide (NaOH) as a main component at 130° C. to 160° C. for 3 minutes or more. According to this black dye treatment, the temperature of the strong alkaline aqueous solution is low, 130° C. to 160° C., so the base material 11 is not heated to a level where it is altered or deformed. Therefore, changes in the structure, strength, properties, etc. of the base material 11 are suppressed, and the structure, strength, properties, etc. of the base material 11 obtained by the carbonitriding heat treatment are maintained even after the black dye treatment. In addition, the thickness of the black oxide film 12 formed by the black dye treatment is thin, 1 μm to 2 μm. Therefore, the surface state of the base material 11 in contact with the black oxide film 12 is almost the same as the surface state of a steel material that has been subjected to carbonitriding heat treatment.
[0038] The base material 11 is preferably made of, for example, chromium molybdenum, and is preferably subjected to a special carbonitriding heat treatment shown in Fig. 6, which will be described later, before the formation of the black oxide film 12. This special carbonitriding heat treatment enhances the refinement of crystal grains in the base material 11 and enriches precipitated compounds. This enhances the surface damage resistance, improves fatigue strength, and suppresses deformation due to bending, thereby further improving the life.
[0039] The base material 11 that has been subjected to the above-mentioned special carbonitriding heat treatment will be described below.
[0040] The diffusion layer DR has a plurality of martensite blocks in addition to a plurality of compound grains. The average grain size of the compound grains in the diffusion layer DR is 0.3 μm or less. The average grain size of the compound grains in the diffusion layer DR is preferably 0.25 μm or less. The area ratio of the compound grains in the diffusion layer DR is 3% or more. The area ratio of the compound grains in the diffusion layer DR is preferably 8% or more. The area ratio of the compound grains in the diffusion layer DR is, for example, 10% or less.
[0041] The average particle size and area ratio of the compound particles in the diffusion layer DR are measured by the following method. First, the cross-section of the diffusion layer DR is polished. Second, the polished surface is corroded. Third, the corroded polished surface is photographed by SEM (Scanning Electron Microscopy) (hereinafter, the image obtained by SEM photography is referred to as "SEM image"). The SEM image is photographed so as to include a sufficient number (20 or more) of compound particles. Fourth, the obtained SEM image is subjected to image processing to calculate the area of each compound particle in the SEM image and the total area of the compound particles.
[0042] Between the circle equivalent diameter of the compound particle and the area of the compound particle, there is a relationship of π × (circle equivalent diameter of the compound particle) 2 The relationship is established: 4 / π=area of compound particles. Therefore, the square root of the area of each compound particle displayed in the SEM image divided by 4 / π is calculated to calculate the circle-equivalent diameter of each compound particle displayed in the SEM image. The value obtained by dividing the sum of the circle-equivalent diameters of each compound particle displayed in the SEM image by the number of compound particles displayed in the SEM image is regarded as the average particle size of the compound particles in the diffusion layer DR. The value obtained by dividing the total area of the compound particles displayed in the SEM image by the area of the SEM image is regarded as the area ratio of the compound particles in the diffusion layer DR.
[0043] The martensite block is a martensite phase block composed of crystals with aligned crystal orientations. The martensite phase is a non-equilibrium phase obtained by quenching the austenite phase of iron in which carbon is dissolved. When the deviation between the crystal orientation of the first martensite phase block and the crystal orientation of the second martensite phase block adjacent to the first martensite phase block is 15° or more, the first martensite phase block and the second martensite phase block are different martensite blocks. On the other hand, when the deviation between the crystal orientation of the first martensite phase block and the crystal orientation of the second martensite phase block adjacent to the first martensite phase block is less than 15°, the first martensite phase block and the second martensite phase block constitute one martensite block.
[0044] The maximum grain size of the martensite blocks in the diffusion layer DR is 3.8 μm or less. The maximum grain size of the martensite blocks in the diffusion layer DR is, for example, 3.6 μm or more.
[0045] The martensite blocks contained in the diffusion layer DR having a crystal grain size of 1 μm or less constitute a first group. The area ratio of the martensite blocks constituting the first group to the total area of the martensite blocks contained in the diffusion layer DR is preferably 0.55 to 0.75.
[0046] The martensite blocks included in the diffusion layer DR may be divided into a second group and a third group. The maximum value of the grain size of the martensite blocks belonging to the second group is smaller than the minimum value of the grain size of the martensite blocks belonging to the third group. The value obtained by dividing the total area of the martensite blocks belonging to the third group by the total area of the martensite blocks included in the diffusion layer DR is 0.5 or more. The value obtained by dividing the total area of the martensite blocks belonging to the third group, excluding the martensite block belonging to the third group having the largest grain size, by the total area of the martensite blocks included in the diffusion layer DR is less than 0.5.
[0047] From another perspective, the martensite blocks included in the second group and the martensite blocks belonging to the third group are classified by the following method. That is, first, each martensite block is assigned to the first group in order from the one with the smallest grain size, and the total area of the martensite blocks assigned to the second group relative to the total area of the martensite blocks is calculated in order. Second, when the ratio of the total area of the martensite blocks assigned to the second group to the total area of the martensite blocks reaches a limit not exceeding 50%, the assignment of martensite blocks to the second group is stopped. Third, the martensite blocks not assigned to the second group are assigned to the third group.
[0048] Preferably, the average grain size of the martensite blocks included in the third group is 0.7 μm or more and 1.4 μm or less. Preferably, the average aspect ratio of the martensite blocks included in the third group is 2.5 or more and 2.8 or less.
[0049] The martensite blocks included in the diffusion layer DR may be divided into a fourth group and a fifth group. The maximum value of the grain size of the martensite blocks belonging to the fourth group is smaller than the minimum value of the grain size of the martensite blocks belonging to the fifth group. The value obtained by dividing the total area of the martensite blocks belonging to the fifth group by the total area of the martensite blocks included in the diffusion layer DR is 0.7 or more. The value obtained by dividing the total area of the martensite blocks belonging to the fifth group, excluding the martensite block belonging to the fifth group having the largest grain size, by the total area of the martensite blocks included in the diffusion layer DR is less than 0.7.
[0050] From another perspective, the martensite blocks included in the fourth group and the martensite blocks belonging to the fifth group are classified by the following method. That is, first, each martensite block is assigned to the fourth group in order from the one with the smallest grain size, and the total area of the martensite blocks assigned to the fourth group relative to the total area of the martensite blocks is calculated in order. Second, when the ratio of the total area of the martensite blocks assigned to the fourth group relative to the total area of the martensite blocks reaches a limit not exceeding 30%, the assignment of martensite blocks to the fourth group is stopped. Third, the martensite blocks not assigned to the fourth group are assigned to the fifth group.
[0051] Preferably, the average grain size of the martensite blocks included in the fifth group is 0.7 μm or more and 1.1 μm or less. Preferably, the average aspect ratio of the martensite blocks included in the fifth group is 2.4 or more and 2.6 or less.
[0052] The grain size and aspect ratio of the martensite blocks in the diffusion layer DR are measured by using the EBSD (Electron Backscattered Diffraction) method.
[0053] First, a cross-sectional image of the diffusion layer DR is taken based on the EBSD method (hereinafter, referred to as an "EBSD image"). The EBSD image is taken so as to include a sufficient number (20 or more) of martensite blocks. Based on the EBSD image, the deviation in the crystal orientation of adjacent martensite phase blocks is identified. As a result, the boundaries of each martensite block are identified. Second, based on the identified boundaries of the martensite blocks, the area and shape of each martensite block displayed in the EBSD image are calculated.
[0054] More specifically, the area of each martensite block shown in the EBSD image is divided by 4 / π, and the square root of the area is calculated to calculate the circle-equivalent diameter of each martensite block shown in the EBSD image. The largest circle-equivalent diameter of the martensite blocks shown in the EBSD image is regarded as the maximum grain size of the martensite blocks in the diffusion layer DR.
[0055] Based on the circle equivalent diameter of each martensite block calculated as described above, among the martensite blocks displayed in the EBSD image, the martensite blocks belonging to the first group are determined. The value obtained by dividing the total area of the martensite blocks belonging to the first group among the martensite blocks displayed in the EBSD image by the total area of the martensite blocks displayed in the EBSD image is the value obtained by dividing the total area of the martensite blocks in the diffusion layer DR belonging to the first group by the total area of the martensite blocks in the diffusion layer DR.
[0056] Based on the circle equivalent diameter of each martensite block calculated as described above, the martensite blocks displayed in the EBSD images are classified into the second and third groups (or into the fourth and fifth groups). The sum of the circle equivalent diameters of the martensite blocks displayed in the EBSD images classified into the third group (or the fifth group) divided by the number of martensite blocks displayed in the EBSD images classified into the third group (or the fifth group) is regarded as the average grain size of the martensite blocks in the diffusion layer DR belonging to the third group (or the fifth group).
[0057] From the shape of each martensite block displayed in the EBSD image, the shape of each martensite block displayed in the EBSD image is approximated as an ellipse by the least squares method. This ellipse approximation by the least squares method is performed according to the method described in S. Biggin and DJ Dingley, Journal of Applied Crystallography, (1977)10, 376-378. In this ellipse shape, the aspect ratio of each martensite block displayed in the EBSD image is calculated by dividing the dimension of the major axis by the dimension of the minor axis. The sum of the aspect ratios of the martensite blocks displayed in the EBSD images classified in the third group (or the fifth group) divided by the number of martensite blocks displayed in the EBSD images classified in the third group (or the fifth group) is regarded as the average aspect ratio of the martensite blocks in the diffusion layer DR belonging to the third group (or the fifth group).
[0058] The diffusion layer DR contains a plurality of prior austenite grains. The prior austenite grains are regions defined by crystal grain boundaries (prior austenite grain boundaries) of austenite grains formed in holding steps S13a and S14a (FIG. 5) described below. The prior austenite grains preferably have an average grain size of 8 μm or less. The prior austenite grains more preferably have an average grain size of 6 μm or less.
[0059] The average grain size of the prior austenite grains in the diffusion layer DR is measured by the following method. First, a cross-section of the diffusion layer DR is polished. Second, the polished surface is corroded. Third, an optical microscope image is taken of the corroded polished surface (hereinafter, an image obtained by optical microscope imagery is referred to as an "optical microscope image"). The optical microscope image is taken so as to include a sufficient number (20 or more) of prior austenite grains. Fourth, the obtained optical microscope image is subjected to image processing to calculate the area of each prior austenite grain in the optical microscope image.
[0060] The area of each prior austenite grain displayed in the optical microscope image is divided by 4 / π, and the square root of the result is calculated to calculate the circle equivalent diameter of each prior austenite grain displayed in the optical microscope image. The sum of the circle equivalent diameters of each prior austenite grain displayed in the optical microscope image divided by the number of prior austenite grains displayed in the optical microscope image is regarded as the average grain size of the prior austenite grains in the diffusion layer DR.
[0061] The average carbon concentration in the diffusion layer DR between the surface (outer peripheral surface) of the base material 11 and a depth position at a distance of 10 μm from the surface of the base material 11 is preferably 0.7 mass% or more. The average carbon concentration in the diffusion layer DR between the surface (outer peripheral surface) of the base material 11 and a depth position at a distance of 10 μm from the surface of the base material 11 is preferably 1.2 mass% or less.
[0062] The average nitrogen concentration in the diffusion layer DR between the surface (outer peripheral surface) of the base material 11 and a depth position at a distance of 10 μm from the surface of the base material 11 is preferably 0.2 mass% or more. The average nitrogen concentration in the diffusion layer DR between the surface (outer peripheral surface) of the base material 11 and a depth position at a distance of 10 μm from the surface of the base material 11 is preferably 0.4 mass% or less.
[0063] The average carbon concentration and average nitrogen concentration in the diffusion layer DR between the surface (outer peripheral surface) of the base material 11 and a depth position 10 μm from the surface of the base material 11 are measured using an EPMA (Electron Probe Micro Analyzer).
[0064] <Method of manufacturing the transmission shaft 1> Next, a manufacturing method of the transmission shaft 1 according to one embodiment will be described with reference to FIGS.
[0065] Fig. 4 is a flow diagram showing a method for manufacturing a transmission shaft according to one embodiment. Fig. 5 is a flow diagram showing a subdivision of the carbonitriding heat treatment steps in Fig. 4. Fig. 6 is a graph showing a heat pattern in the method for manufacturing a transmission shaft according to one embodiment.
[0066] 4, the manufacturing method for a transmission shaft according to this embodiment includes step S1 of preparing a steel material, step S2 of performing a carbonitriding heat treatment, step S3 of performing grinding, super finishing, honing, etc., and step S4 of forming black oxide film 12. In step S1, a steel material made of any one of chromium steel, chromium molybdenum steel, and nickel chromium molybdenum steel is prepared.
[0067] In step S2, the steel material prepared in step S1 is subjected to carbonitriding heat treatment. In this carbonitriding heat treatment, an atmospheric gas containing, for example, ammonia (NH3) gas is used. In step S3, the steel material that has been subjected to carbonitriding heat treatment is subjected to grinding, super finishing, honing, etc. As a result, the steel material is finished to the outer diameter dimensions of the transmission shaft 1.
[0068] Thereafter, in step S4, a black iron oxide film 12 is formed on the surface of the steel material. The black iron oxide film 12 is formed, for example, by a chemical conversion treatment known as a black dye treatment method. In this embodiment, the steel material is immersed for 3 minutes or more in a strong alkaline aqueous solution containing sodium hydroxide as a main component at a temperature of 130° C. to 160° C. As a result, as shown in FIG. 3, a black iron oxide film 12 is formed on the surface of the base material 11, and the transmission shaft 1 of this embodiment is manufactured.
[0069] As the carbonitriding heat treatment in step S2, a special carbonitriding heat treatment shown in Figures 5 and 6 may be performed. Hereinafter, this special carbonitriding heat treatment will be described.
[0070] As shown in FIG. 5, the special carbonitriding heat treatment includes a carbonitriding step S11, a diffusion step S12, a primary quenching step S13, a secondary quenching step S14, and a tempering step S15.
[0071] In the carbonitriding step S11, for example, carbonitriding is performed on the surface of a steel material made of chromium-molybdenum steel prepared in step S1 shown in Fig. 4. The carbonitriding step S11 is performed by holding the steel material in a furnace at a predetermined temperature (hereinafter referred to as "first holding temperature") for a predetermined time (hereinafter referred to as "first holding time"). For example, a gas containing endothermic transformation gas (R gas) and ammonia is used as the atmosphere in the furnace. The first holding temperature is, for example, 930°C or higher and 940°C or lower. The first holding time is, for example, 10 hours or higher and 15 hours or lower.
[0072] In the diffusion step S12, the carbon and nitrogen introduced from the surface of the steel material in the carbonitriding step S11 diffuse into the inside of the steel material. The diffusion step S12 is performed by holding the steel material in a furnace at a predetermined temperature (hereinafter referred to as the "second holding temperature") for a predetermined time (hereinafter referred to as the "second holding time"). For example, a gas containing an endothermic converted gas (R gas) and ammonia is used as the furnace atmosphere. The second holding temperature is, for example, 930°C or higher and 940°C or lower. The second holding time is, for example, 5 hours or higher and 10 hours or lower.
[0073] In the diffusion step S12, α defined by the following formulas (1) and (2) is adjusted to be lower than that in the carbonitriding step S11. As is clear from formulas (1) and (2), α is adjusted by adjusting the amount of carbon monoxide, the amount of carbon dioxide, and the amount of undecomposed ammonia in the atmosphere. The amount of undecomposed ammonia in the atmosphere is preferably 0.1 volume % or more.
[0074]
number
[0075] In the primary quenching step S13, quenching is performed on the steel material. The primary quenching step S13 includes a holding step S13a and a cooling step S13b. The holding step S13a is performed by holding the steel material in a furnace at a predetermined temperature (hereinafter referred to as the "third holding temperature") for a predetermined time (hereinafter referred to as the "third holding time"). In the primary quenching step S13, the atmosphere in the furnace does not contain ammonia. The third holding temperature is a temperature equal to or higher than the A1 transformation point of the steel constituting the steel material and is lower than the first holding temperature and the second holding temperature. The third holding temperature is, for example, 850°C or higher and lower than 930°C. Preferably, the third holding temperature is 860°C or higher and 880°C or lower. The third holding time is, for example, 0.5 hours or higher and 2 hours or lower. In the cooling step S13b, the steel material is cooled from the third holding temperature to a temperature equal to or lower than the Ms point. The cooling step S13b is performed, for example, by oil cooling.
[0076] In the secondary quenching step S14, the steel material is quenched. The secondary quenching step S14 includes a holding step S14a and a cooling step S14b. The holding step S14a is performed by holding the steel material in a furnace at a predetermined temperature (hereinafter referred to as a "fourth holding temperature") for a predetermined time (hereinafter referred to as a "fourth holding time"). In the secondary quenching step S14, the atmosphere in the furnace does not contain ammonia. The fourth holding temperature is a temperature equal to or higher than the A1 transformation point of the steel material constituting the steel material and lower than the third holding temperature. The fourth holding temperature is, for example, equal to or higher than the A1 transformation point of the steel material constituting the steel material and lower than 850°C. The fourth holding temperature is preferably equal to or higher than 820°C and lower than 840°C. The fourth holding time is, for example, 1 hour or more and 2 hours or less. In the cooling step S14b, the steel material is cooled from the fourth holding temperature to a temperature equal to or lower than the Ms point. The cooling step S14b is performed, for example, by oil cooling.
[0077] The compound particles in the diffusion layer DR are mainly precipitated in the holding step S13a and the holding step S14a. The solid solubility limit of carbon and nitrogen in steel increases as the holding temperature increases (decreases as the holding temperature decreases). The third holding temperature is set higher than the holding temperature in normal quenching in order to prevent excessive precipitation of compound particles in the diffusion layer DR in the holding step S13a (set so that the solid solubility limit of carbon and nitrogen in steel is relatively wider than that in normal quenching).
[0078] In the holding step S14a, the compound particles have already precipitated in the holding step S13a. That is, in the holding step S14a, the carbon concentration and the nitrogen concentration in the base material are reduced, and the compound particles are relatively less likely to precipitate than in the holding step S13a. Therefore, the fourth holding temperature is set lower than the third holding temperature in order to narrow the solid solubility limit of nitrogen and carbon in the steel and promote the precipitation of the compound particles in the holding step S14a. This makes it possible to make the area ratio of the compound particles in the diffusion layer DR 3% or more. In addition, by setting the fourth holding temperature lower than the third holding temperature, it is possible to suppress the coarsening of the compound particles precipitated in the holding steps S13a and S14a, and therefore the average particle size of the compound particles in the diffusion layer DR can be made 0.3 μm or less.
[0079] In the holding step S13a and the holding step S14a, the growth of the austenite grains is suppressed by the pinning effect of the compound grains precipitated in a large amount and finely as described above, and the austenite grains are kept fine. During the martensitic transformation, a plurality of martensite blocks are formed within one austenite grain. From another perspective, one martensite block is not formed across a plurality of austenite grains. Therefore, the more the austenite grains are refined, the more the martensite blocks contained therein are refined.
[0080] In the tempering step S15, the steel material is tempered. The tempering step S15 is performed by holding the steel material in a furnace at a predetermined temperature (hereinafter referred to as the "fifth holding temperature") for a predetermined time (hereinafter referred to as the "fifth holding time") and then cooling the steel material. The fifth holding temperature is a temperature equal to or lower than the A1 transformation point of the steel constituting the steel material. The fifth holding temperature is, for example, 150°C or higher and 350°C or lower. The fourth holding time is, for example, 0.5 hours or higher and 5 hours or lower. The cooling in the tempering step S15 is performed by, for example, air cooling.
[0081] Through the above steps S11 to S15, the carbonitriding heat treatment shown in step S2 of FIG. 4 is performed.
[0082] Fig. 6 is a graph showing a heat pattern in the manufacturing method of the transmission shaft according to the embodiment. Fig. 6 shows a schematic diagram of the relationship between the first holding temperature to the fifth holding temperature and the first holding time to the fifth holding time.
[0083] <Effects of this embodiment> Next, the function and effect of the transmission shaft of this embodiment will be described with reference to FIGS.
[0084] Figure 7 is a diagram showing the driving force of the needle rollers and the load distribution acting on the raceway surface when the raceway surface is straight (A) and when it is deflected (B). As shown in Figure 7(A), when the raceway surface 1b is straight in the axial direction, the load distribution applied to the raceway surface 1b through the rollers (rolling elements) 2 is almost uniform. As a result, the driving force of the rollers 2 is also almost uniform in the axial direction of the rollers 2.
[0085] In contrast, as shown in Figure 7(B), a load is applied to approximately the center of the transmission shaft 1 with both ends of the shaft fixed. For this reason, the raceway surface 1b is deflected in the axial direction, and the transmission shaft 1 is used in a state where bending stress is acting on it. When the raceway surface 1b is deflected, skew is likely to occur due to the difference in the shape of the rollers 2 rolling on the raceway surface 1b on the left and right, resulting in greater slippage. This makes it easier for the oil film to break, and increases the risk of surface damage due to metal contact.
[0086] The black iron oxide film 12 has a porous surface and a structure including recesses on the surface. Therefore, by forming the black iron oxide film 12, oil is retained in the recesses on the surface, improving the oil film forming ability and improving the life under lean lubrication conditions.
[0087] In addition, the black iron oxide film 12 is softer than the mating material (needle roller). Therefore, uneven parts due to machining or convex parts around the indentation created when a foreign object is caught wears away early, and metal contact in actual use can be reduced. In a life test, wear of about 0.8 μm occurred in the black iron oxide film 12 in the early stages of operation, and the wear did not progress until damage occurred. For this reason, the thickness of the black iron oxide film 12 must be 0.8 μm or more (preferably 1 μm or more). In addition, if the black iron oxide film 12 is made thicker, the time required for black dyeing will be longer, leading to increased costs, so the thickness of the black iron oxide film 12 is desirably 2 μm or less.
[0088] The black dyeing process makes it possible to process multiple products at once, which helps prevent increases in costs due to additional processing. In addition, the surface roughness is improved during the black dyeing process, which helps reduce the number of steps required to process the transmission shaft 1.
[0089] When a unidirectional load acts for a long time, there is a concern that minute plastic deformation (creep) will increase over time. However, in the transmission shaft 1 that has been subjected to the special carbonitriding heat treatment shown in Figures 5 and 6, the grain size is refined and the amount of precipitated compounds is increased, resulting in a higher yield stress in the surface layer where the maximum bending stress acts. This makes it possible to suppress creep deformation more than in products that have been subjected to general carbonitriding treatment, and to minimize deformation due to long-term deflection. In addition, the special carbonitriding heat treatment shown in Figures 5 and 6 improves the fatigue strength and surface damage resistance of the base material 11 compared to conventional carbonitriding treatment, further improving the lifespan. EXAMPLES
[0090] An experiment conducted to confirm the effects of the transmission shaft 1 according to the embodiment (hereinafter referred to as "this experiment") will be described below.
[0091] <Sample> In this experiment, Sample 1 and Sample 2 were used. The steel material used for Sample 1 and Sample 2 was SCM435 (JIS G 4053:2016), as shown in Table 1. Each of Sample 1 and Sample 2 is a rotating shaft that is an inner member of a needle roller bearing device.
[0092] [Table 1]
[0093] As shown in Table 2, for each of Sample 1 and Sample 2, the carbonitriding step S11 was performed under conditions of a first holding temperature of 930°C or more and 940°C or less and a first holding time of 13 hours. For each of Sample 1 and Sample 2, the diffusion step S12 was performed under conditions of a second holding temperature of 930°C or more and 940°C or less and a second holding time of 6 hours. The amounts of carbon monoxide, carbon dioxide and ammonia in the atmosphere in the carbonitriding step S11 and the diffusion step S12 were set to 11 vol% or more and 17 vol% or less, 0.05 vol% or more and 0.15 vol% or less, and 0.1 vol% or more and 0.3 vol% or less, respectively.
[0094] Each of Sample 1 and Sample 2 was subjected to a primary quenching step S13 under conditions of a third holding temperature of 870°C and a third holding time of 1 hour. Thereafter, Sample 1 was subjected to a secondary quenching step S14 under conditions of a fourth holding temperature of 830°C and a fourth holding time of 1.5 hours. Sample 2 was not subjected to this secondary quenching step S14. Thereafter, each of Sample 1 and Sample 2 was subjected to a tempering step S15 under conditions of a fifth holding temperature of 180°C and a fifth holding time of 3 hours. Thereafter, each of Sample 1 and Sample 2 was subjected to mechanical polishing with a polishing amount of 150 μm as a processing step S3.
[0095] [Table 2]
[0096] <Measurement of carbon and nitrogen concentrations> Fig. 8 is a graph showing the results of measuring the carbon concentration and nitrogen concentration by EPMA for sample 1. Fig. 9 is a graph showing the results of measuring the carbon concentration and nitrogen concentration by EPMA for sample 2. In Figs. 8 and 9, the horizontal axis represents the distance from the surface of sample 1 and sample 2 (unit: mm), and the vertical axis represents the carbon concentration and nitrogen concentration (unit: mass % concentration).
[0097] As shown in FIG. 8, many sharp peaks were confirmed in the carbon concentration and nitrogen concentration near the surface of sample 1. From this result, it was experimentally confirmed that fine compound particles such as carbides, nitrides, and carbonitrides were precipitated near the surface of sample 1. Furthermore, in sample 1, the average carbon concentration in the region between the surface and a depth position at a distance of 10 μm from the surface was in the range of 0.7% to 1.2%, and the average nitrogen concentration in the region was in the range of 0.2 mass% to 0.4 mass%. On the other hand, as shown in FIG. 9, many sharp peaks were not confirmed in the carbon concentration and nitrogen concentration near the surface of sample 2. From this result, it was experimentally confirmed that fine compound particles such as carbides, nitrides, and carbonitrides were not precipitated near the surface of sample 2.
[0098] <Structural Observation> Fig. 10 is an electron microscope image of the surface vicinity of sample 1. As shown in Fig. 10, it was confirmed that a large number of compound particles having a size of 0.2 μm or more and 3.0 μm or less were precipitated in the surface vicinity of sample 1. It was also confirmed that the average particle size of the compound particles in the surface vicinity of sample 1 was approximately 0.25 μm. It was also confirmed that the area ratio of the compound particles in the surface vicinity of sample 1 was approximately 8%.
[0099] Fig. 11 is an electron microscope image of the surface vicinity of sample 2. As shown in Fig. 11, it was confirmed that the area ratio of compound particles in the surface vicinity of sample 2 was about 1%.
[0100] Furthermore, when the EBSD image of the vicinity of the surface of sample 1 was examined, it was confirmed that the maximum grain size of the martensite blocks near the surface of sample 1 was in the range of 3.6 μm to 3.8 μm. It was also confirmed that 90% or more of the area of the martensite blocks near the surface of sample 1 was occupied by martensite blocks with a grain size of 2 μm or less. Furthermore, it was confirmed that 55% to 75% of the area of the martensite blocks near the surface of sample 1 was occupied by martensite blocks with a grain size of 1 μm or less.
[0101] Furthermore, when the EBSD image of the vicinity of the surface of sample 2 was examined, it was confirmed that the maximum grain size of the martensite blocks near the surface of sample 2 was in the range of 5.1 μm to 7.3 μm. It was also confirmed that 65% to 80% of the area of the martensite blocks near the surface of sample 2 was occupied by martensite blocks with a grain size of 2 μm or less. Furthermore, it was confirmed that 35% to 45% of the area of the martensite blocks near the surface of sample 2 was occupied by martensite blocks with a grain size of 1 μm or less.
[0102] Fig. 12 is an optical microscope image of the surface vicinity of sample 1. As shown in Fig. 12, it was confirmed that the average grain size of the prior austenite grains in the surface vicinity of sample 1 was in the range of 4 µm or more and 8 µm or less, and the crystal grain size of the prior austenite grains was distributed in the range of 1 µm or more and 10 µm or less. Fig. 13 is an optical microscope image of the surface vicinity of sample 2. As shown in Fig. 13, it was confirmed that the average grain size of the prior austenite grains in the surface vicinity of sample 2 was in the range of 12 µm or more and 25 µm or less, and the crystal grain size of the prior austenite grains was distributed in a wide range of 5 µm or more and 100 µm or less.
[0103] Fig. 14 is a graph showing the average grain size of martensite blocks belonging to the third and fifth groups in the vicinity of the surface of Sample 1 and Sample 2. In Fig. 14, the vertical axis shows the average grain size (unit: µm).
[0104] 14, the average grain size of the martensite blocks belonging to the third group was about 1.0 μm near the surface of Sample 1. This confirmed that the average grain size of the martensite blocks belonging to the third group in Sample 1 was in the range of 0.7 μm to 1.4 μm.
[0105] 14, the average grain size of the martensite blocks belonging to the fifth group was about 0.8 μm near the surface of Sample 1. This confirmed that the average grain size of the martensite blocks belonging to the fifth group in Sample 1 was in the range of 0.6 μm to 1.1 μm.
[0106] On the other hand, in the vicinity of the surface of Sample 2, the average grain size of the martensite blocks belonging to the third group was about 1.7 μm, and in the vicinity of the surface of Sample 2, the average grain size of the martensite blocks belonging to the fifth group was about 1.3 μm.
[0107] Fig. 15 is a graph showing the average aspect ratios of martensite blocks belonging to the third and fifth groups in the vicinity of the surfaces of Samples 1 and 2. In Fig. 15, the vertical axis shows the average aspect ratio.
[0108] 15, the average aspect ratio of the martensite blocks belonging to the third group was approximately 2.8 in the vicinity of the surface of Sample 1. This confirmed that the average aspect ratio of the martensite blocks belonging to the third group in Sample 1 was in the range of 2.5 to 2.8.
[0109] 15, the average aspect ratio of the martensite blocks belonging to the fifth group was about 2.6 in the vicinity of the surface of Sample 1. This confirmed that the average aspect ratio of the martensite blocks belonging to the fifth group in Sample 1 was in the range of 2.4 to 2.6.
[0110] On the other hand, in the vicinity of the surface of Sample 2, the average aspect ratio of the martensite blocks belonging to the third group was about 3.2, and in the vicinity of the surface of Sample 2, the average aspect ratio of the martensite blocks belonging to the fifth group was about 3.0.
[0111] <Rolling fatigue life test under lubrication with foreign matter> A rolling fatigue test under contaminated lubrication (hereinafter referred to as "rolling fatigue test") was conducted using the transmission shaft, needle roller bearing with cage, and outer member of each of samples 1 to 4. Sample 3 is a transmission shaft obtained by subjecting sample 1 to a black dyeing treatment, and sample 4 is a transmission shaft obtained by subjecting sample 2 to a black dyeing treatment. The black dyeing treatment applied to each of samples 3 and 4 was performed by immersing the samples in a strong alkaline aqueous solution containing sodium hydroxide as the main component at approximately 130°C for 10 minutes or more. The thickness of the black oxide film formed by this black dyeing treatment was 1.8 μm.
[0112] In the rolling fatigue test, the lubrication was oil bath lubrication using engine oil SAE30, the load was 24.5 kN, and the relative rotation speed of the outer member with respect to the transmission shaft was 2150 rpm.
[0113] In the rolling fatigue test, L 10 Life (the test time when the cumulative probability of failure is 10% after statistical analysis of the time from the start of the test to the occurrence of peeling), L 50 Evaluation was based on the lifespan (the time from the start of the test to when peeling occurs was statistically analyzed, and the test time when the cumulative probability of failure was 50%). The results are shown in Table 3 below.
[0114] [Table 3]
[0115] From the results in Table 3, it was found that the life of sample 4, which was subjected to general carbonitriding and black dyeing, was improved compared to sample 2, which was subjected to general carbonitriding and not black dyeing. It was also found that the life of sample 3, which was subjected to carbonitriding heat treatment and black dyeing as shown in Figures 5 and 6, was significantly improved compared to sample 2. It was also found that the life of sample 3 was improved compared to sample 1, which was subjected to carbonitriding heat treatment and not black dyeing as shown in Figures 5 and 6.
[0116] From the above, it was found that the service life is improved by applying black dyeing treatment compared to when it is not applied. It was also found that the service life is significantly improved by applying black dyeing treatment after applying the special carbonitriding heat treatment shown in Figures 5 and 6.
[0117] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]
[0118] 1 transmission shaft, 1a oil passage, 1b, 4b raceway, 2 needle roller, 3 cage, 3a pocket, 4 planetary gear, 4a tooth, 10 bearing device, 11 base material, 12 black oxide coating, DR diffusion layer, IP interior.
Claims
1. A transmission shaft used in a transmission, the shaft having a raceway surface on which needle rollers roll, A base material made of any one of chrome steel, chrome-molybdenum steel, and nickel-chrome-molybdenum steel, and having a diffusion layer on a surface thereof, the diffusion layer including at least one crystal grain of iron carbide, iron nitride, and iron carbonitride; a black oxide coating formed on the surface of the base material and disposed on at least the raceway surface, The chromium content of the base material is 0.90 wt % or more and 1.20 wt % or less, The thickness of the black oxide coating is 1 μm or more and 2 μm or less.
2. 2. The transmission shaft according to claim 1, wherein the base material is made of chrome-molybdenum steel.
3. 3. The transmission shaft according to claim 2, wherein an average grain size of prior austenite crystal grains on the surface of the base material is 8 μm or less.
4. 4. The transmission shaft according to claim 2, wherein an area ratio of compound grains including said at least one crystal grain in said diffusion layer is 3% or more, and an average grain size of said compound grains is 0.3 μm or less.
5. The transmission shaft according to claim 2 , wherein the diffusion layer includes a plurality of martensite blocks.
6. 6. The transmission shaft according to claim 5, wherein the martensite blocks have a maximum grain size of 3.8 μm or less.
7. A transmission shaft according to any one of claims 1 to 6; a plurality of needle rollers that roll on the raceway surface of the transmission shaft.
Citation Information
Patent Citations
Heat radia tion material
JP1977072339A
Roller bearings for vehicle transmissions
JP1991052416U
Needle roller bearing
JP2006161887A
Roller bearing
JP2012215288A
Shaft for bearing
JP2017106534A